Response and point of no return (PNR) of penaeid shrimp under artificial cold treatment - Huq, K A; Molla, M F A; Islam, M Aminul; Hossain, M A (Indian Journal of Fisheries, 2011)
For easy handling and transportation oflive shrimp, it is essential to know the lowesttemperature to which they remain physiologicallyactive but require minimum oxygen andstop movement of body and appendages. Thiscan be done artificially by lowering temperature,thus forcing shrimp to temporary hibernationand facilitating its transport in Uvecondition. It is also vital to know how manyshrimp return to normal after cold treatmentand the lowest temperature beyond which noshrimp will regain consciousness even if thetemperature is raised, i.e. the point of noreturn. This study deals with determination ofpoint of no return for post larvae, juvenile andmarket sized Penaeus monodon and juvenilePendeus indicus. No information is availableon this subject.